EKSISTENSI PEMILIHAN DENGAN MODEL KESEPAKATAN WARGA DALAM SISTEM PEMILIHAN UMUM DI INDONESIA (KAJIAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 47-81/PHPU.A-VII/2009 TENTANG PERSELISIHAN HASIL PEMILIHAN UMUM) - Firdaus, Emilda; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Indonesia is a democratic country that wants elections by One Man One vote with the principles of direct, general, secret, honest and fair set forth in Article 22E paragraph (1) of the Constitution republic of Indonesia Year 1945. Indonesia with customary pluralistic society , principles that should be the cornerstone of elections can not be applied generally. In a society Yahukimo, Papua Province elections were conducted with a system of collective (community agreement or acclamation). The Constitutional Court by a decision Number. 47-81 / PHPU.A-VII / 2009 gives legitimacy to the election by means of customary (noken system). decision No. 47-81 / PHPU.A-VII / 2009 was recognized by the judges in the constitutional court as a judgment that is casuistry or only applicable in the area in question only. Still, restrict the right of people to choose freely and directly correspond conscience. The purpose of this thesis namely, first, the existence of election with the model agreement of citizens in the electoral system in Indonesia. Second, Is the electoral system with the collective model (community agreement or acclamation) in accordance with the principles of the election in the Act of 1945Keywords : Court Ruling - Noken System - Elections